2003
DOI: 10.1088/0953-2048/17/1/005
|View full text |Cite
|
Sign up to set email alerts
|

Performance tuning and improvement ofJcBcharacteristics for Bi-2212/Ag tapes by controlling the excess oxygen content

Abstract: The dependence of the Jc value on applied magnetic fields (Jc–B characteristics) is investigated for Bi-2212/Ag tapes prepared by the melt-solidification method with respect to the effect of annealing after heat treatment (post-annealing). The results of the present work show that annealing under a high-oxygen partial-pressure and low-temperature condition enhances the Jc–B characteristics of Bi-2212/Ag tapes, and the sample annealed under a condition of p(O2) = 1 atm and 300 °C exhibited the highest Jc–B char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…H k (20 K) is initially improved by the 400 • C secondary HT compared to the primary HT, rising from 8.5 T to 9.5 T. However, after this initial increase, H k decreases monotonically with increasing secondary HT temperature. Using H k to approximate H irr , we interpret this decrease as a continuous decline in vortex pinning strength with an increasing electronic anisotropy induced by the decreasing carrier density [29,36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…H k (20 K) is initially improved by the 400 • C secondary HT compared to the primary HT, rising from 8.5 T to 9.5 T. However, after this initial increase, H k decreases monotonically with increasing secondary HT temperature. Using H k to approximate H irr , we interpret this decrease as a continuous decline in vortex pinning strength with an increasing electronic anisotropy induced by the decreasing carrier density [29,36].…”
Section: Resultsmentioning
confidence: 99%
“…With the expectation that global underdoping treatments would remove this compensation, we here investigate how optimized high J c , oxygen-overdoped Bi-2212 round wires behave when systematically underdoped so as to better understand the extent to which oxygen doping affects GB connectivity, vortex pinning and transport J c . Previous studies on Bi-2212 have reported increased H irr in Bi-2212 tapes [29,34], single crystals [31,32,35], and round wires [11,39], improved J c (H) [11,[29][30][31][33][34][35], and changes in critical temperature (T c ) [11,27,29,30,33,[35][36][37]40] with increasing oxygen doping level. For the present study, as illustrated in Figure 1, optimally overdoped (with respect to J c ) and full-density, overpressure-processed Bi-2212 round wires originally processed at 100 bar total pressure (with 1 bar O 2 , balance Ar) were each subjected to a secondary heat treatment (HT) at a low oxygen partial pressure (pO 2 ) to progressively underdope them, with the expectation that higher secondary heat treatment temperature would result in lower oxygen content in both grains and grain boundaries.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…T. Nakane et al. reported that a high-oxygen partial-pressure and low-temperature condition was effective to improve the characteristics of Bi-2212/Ag tape as a consequence of the increase in excess oxygen content [8]. However D. Buhl et al reported that they acquired the highest critical current when they carry out either by switching the atmosphere at 700 from oxygen to nitrogen during cooling to room temperature or by further annealing at 500 in nitrogen for 20 h [9], [10].…”
Section: Resultsmentioning
confidence: 99%
“…This results in an increase of J c values. Indeed, post-annealing in a high P O2 atmosphere is effective in increasing the J c values of Bi-2212/Ag tapes [6,7]. From the shift of T c values shown in figures 4 and 5, the air quenching from the T end of 830 • C probably decreases the oxygen content more for the tapes when processed at P O2 = 0.21 atm, compared with the processing at P O2 = 1 atm.…”
mentioning
confidence: 92%